Coordination of Plastid and Light Signaling Pathways upon Development of Arabidopsis Leaves under Various Photoperiods - Lepisto A; Rintamaki E (OXFORD UNIV PRESS, 2022)
Plants synchronize their cellular and physiological functions according to the photoperiod ( the length of the light period) in the cycle of 24 h. Photoperiod adjusts several traits in the plant life cycle, including flowering and senescence in annuals and seasonal growth cessation in perennials. Photoperiodic development is controlled by the coordinated action of photoreceptors and the circadian clock. During the past 10 years, remarkable progress has been made in understanding the molecular mechanism of the circadian clock, especially with regard to the transition of Arabidopsis from the vegetative growth to the reproductive phase. Besides flowering photoperiod also modifies plant photosynthetic structures and traits. Light signals controlling biogenesis of chloroplasts and development of leaf photosynthetic structures are perceived both by photoreceptors and in chloroplasts. In this review, we provide evidence suggesting that the photoperiodic development of Arabidopsis leaves mimics the acclimation of plant to various light intensities. Furthermore, the chloroplast-to-nucleus retrograde signals that adjust acclimation to light intensity are proposed to contribute also to the signaling pathways that control photoperiodic acclimation of leaves.